Do Inactive Older Adults Who Increase Physical Activity Experience Less Disability: Evidence From the Osteoarthritis Initiative. Issue 1 (January 2017) - Song, Jing; Gilbert, Abigail L.; Chang, Rowland W.; Pellegrini, Christine A.; Ehrlich-Jones, Linda S.; Lee, Jungwha; Pinto, Daniel; Semanik, Pamela A.; Sharma, Leena; Kwoh, C. Kent; Jackson, Rebecca D.; Dunlop, Dorothy D.
Abstract : Background: Physical inactivity is a leading risk factor for developing disability. Although randomized clinical trials have demonstrated improving physical activity can reduce this risk in older adults with arthritis, these studies did not specifically evaluate inactive adults. Objectives: The aim of this study was to evaluate the relationship of changes in physical activity with disability changes among initially inactive adults with or at high risk of knee osteoarthritis from Osteoarthritis Initiative. Methods: Inactive persons were identified at baseline based on the US Department of Health and Human Services classification (no [zero] 10-minute session of moderate-to-vigorous [MV] activity over 1 week) from objective accelerometer monitoring. Two years later, physical activity change status was classified as follows: (1) met Federal physical activity guidelines (≥150 MV minutes/week acquired in bouts ≥10 minutes), (2) insufficiently increased activity (some but <150 MV bout minutes/week), or (3) remained inactive. Disability at baseline and 2 years was assessed by Late Life Disability Instrument limitation and frequency scores. Multiple regression evaluated the relationship of physical activity change status with baseline–to–2-year changes in disability scores adjusting for socioeconomics, health factors, and baseline disability score. Results: Increased physical activity showed a graded relationship with improved disability scores in Late Life Disability Instrument limitation ( P < 0.001) and frequency scores ( P = 0.027). While increasing MV activity to guideline levels showed the greatest reduction, even insufficiently increased physical activity was related to reduced disability. Conclusions: Findings support advice to increase MV physical activity to reduce disability among inactive adults with or at high risk of knee osteoarthritis, even when guidelines are not met.